ANALISIS PERILAKU PETUGAS TERHADAP PENGELOLAAN LIMBAH MEDIS PADAT DI RSUD TALANG UBI KABUPATEN PALI TAHUN 2023 - afriyanti arfan; Arie Wahyudi; Gema Asiani (Avicenna: Jurnal Ilmiah, 2023)
Background: Solid medical waste, which includes infectious and pathological waste and is owned by public health agencies or private organizations, is a type of waste generated in sanitation facilities or laboratories. The goal is to find out the behavior of officers towards the management of solid medical waste at the Talang Ubi Hospital, Pali Regency, in 2023. Methods: Quantitative methods were used through a cross sectional research design, held at Talang Ubi Hospital, Pali Regency, in June 2023. The study sample was 74 respondents with using proportional random sampling technique to draw members of the population, while to determine the spatial sample using purposive sampling to select individuals in the population, but to use purposive sampling to determine the sample space. Data analysis using univariate, bivariate, and multivariable methods was obtained through interviews and questionnaires. Results: Management of solid medical waste that meets the requirements is 94.6%. There is no relationship between officers' knowledge, years of service and solid medical waste management. There is a significant relationship between the attitude of officers, the actions of officers using PPE and the management of solid medical waste. The results of the multivariate analysis, the variable that has a significant relationship, namely the actions of the cleaning staff and the greatest influence, namely solid medical waste management with good tenure will have good solid medical waste management by 5,520 times higher than those with less solid medical waste management. Conclusion: Hospital solid medical waste management training is needed for health workers to understand the importance of this aspect.   Keywords: Service Behavior, Solid Medical Waste Management, Hospital